DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Mahendra, Juandra Prisma (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study aims to determine the impact of gadgets on early childhood social emotional development. This research is a type of qualitative research with a case study approach, the location of the study was carried out in RA Baytussalam North Lombok, the subjects in this study were RA Baytussalam Dusun Dasan Tengak students totaling 16 students, 1 teacher, and 2 guardians of students. The results of the analysis show that the impact of gadget use on the social emotional development of children in RA Baytussalam consists of positive impacts and negative impacts. The positive use of gadgets is to increase imagination, train intelligence, and improve the ability to recognize letters and numbers. While the negative impacts of using gadgets are being a closed person, having trouble sleeping, children getting angry easily, and being exposed to radiation.